1966
DOI: 10.1111/j.1600-0765.1966.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oral bacterial endotoxin on cell migration and phagocytic activity

Abstract: The capacity of endotoxin from oral bacteria to induce inflammation was studied in human subjects by the “skin, window” technique. The inner surface of the forearm was excoriated with a scalpel and sterile cover slips applied to the wounds. Migrating inflammatory cells were found to adhere to the cover slips and regular replacement of the cover slips permitted longitudinal examination of the cytology of the exudates. Topical application of lipopolysaccharide endotoxin from oral Veillonella to the abraded skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1970
1970
1984
1984

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…Although this study did not attempt to determine the predominant mechanisms by which complement was activated, it is conceivable that the mechanisms may have dif-fered somewhat among the subjects tested. Substantial evidence exists that both immune reactions and endotoxins are involved (Mergenhagen, Hampp & Scherp 1961, Jensen, Theilade & Jensen 1966, Nisengard & Beutner 1970, Platt, Crosby & Dalbow 1970, Berglund 1971, Snyderman, Phillips & Mergenhagen 1971. The presence of endotoxin producing bacteria among gram negative organisms in plaque samples may account for the increase in chemotactic response found when complement sources were mixed with plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not attempt to determine the predominant mechanisms by which complement was activated, it is conceivable that the mechanisms may have dif-fered somewhat among the subjects tested. Substantial evidence exists that both immune reactions and endotoxins are involved (Mergenhagen, Hampp & Scherp 1961, Jensen, Theilade & Jensen 1966, Nisengard & Beutner 1970, Platt, Crosby & Dalbow 1970, Berglund 1971, Snyderman, Phillips & Mergenhagen 1971. The presence of endotoxin producing bacteria among gram negative organisms in plaque samples may account for the increase in chemotactic response found when complement sources were mixed with plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would appear that some substance produced by gramnegative organisms in bacterial plaque causes the initial clinical and histologic signs of gingival inflammation. In a recent investigation on humans, Jense et al, 22 using the "skin window" technique, have shown that the ad ministration of endotoxin caused an immediate and con tinued migration of neutrophils. Furthermore, in an other study, Jensen et al 23 have discovered that after an initial depression in the number of inflammatory cells oral bacterial endotoxin administration causes a stimula tion in the number of inflammatory cells, with increased capacities to phagocytize and destroy bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The theory that endotoxin initiates the gingival inflam matory lesions has been suggested by several other in vestigators. For example, Jensen et al 22 state, on the basis of their findings, that although "precise" evidence of the ability of endotoxin to penetrate the intact sul cular epithelium has not been presented in the literature, "it appears that the amounts of endotoxin present in bacterial plaque are well above those needed to produce (initiate) inflammatory reactions." Although "precise" evidence of the capability of endotoxin to penetrate in tact crevicular epithelium has not yet been presented, it will be recalled that Rizzo 24 in a recent article has shown that 40% of the rabbits with intact epithelium, treated with endotoxin powder, in his study, although failing to show signs of a localized Shwartzman reac tion, did demonstrate a "considerable neutrophil infiltra tion with some edema" in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LPS on PMN migration and phagocytosis was examined by Jensen et al (1966). LPS from Veillonella, applied to skin grazes on the forearms of human volunteers, produced an increase in both PMN migration and phagocytic activity.…”
Section: Introductiotimentioning
confidence: 99%